Nicaragua Social Investment Fund : Conditional Cash Transfer, a New Avenue for Social Funds? - Vermehren, Andrea (World Bank, Washington, DC, 2012)
The note presents the case of the Nicaragua Social Investment Fund (FISE), which accounts for an impressive record, having financed a significant number of projects in ten years (sixty percent of these benefiting the education sector). Moreover, it reinforced rural water, and municipal infrastructure projects, and strengthened its engagement in local capacity building at the municipal, and community levels. However, in the late 90s, it became clear there were limits to the effectiveness of supply side interventions, and both FISE, and the government began thinking about strengthening the demand side, through new ways to improve access to social services, and creating an opportunity for inclusion of the most vulnerable, particularly children living precariously in rural areas. The Conditional Cash Transfer (CCT) program is examined, a new window to finance cash transfers to extremely poor families in selected rural areas. Yet, the remarkable results of CCT questions its affordability, and sustainability. The Government is now starting to prioritize programs, and investments in the social sector to achieve greater impact. As for the question of the program's cost effectiveness, the Government is considering undertaking a comparative analysis to assess results.